Design of photocoustic detecting system based on Android system - Miao, Xilin (2018)
Photoacoustic Imaging is a nondestructive medical imaging method developed in recent years. It has combined merits of high contrast ratio imaging for optical imaging and high penetrability for ultrasonic imaging, and has obvious advantages in terms of structural form, metabolism, and physiological characteristics of biological tissue. Photoacoustic Imaging has promising application prospects and is now becoming research focus in the international biomedical imaging field. As medical detecting system is now developing towards miniaturization and portability, the study of medical photoacoustic system is of great significance. Furthermore, with the rapid development of the mobile terminal, the Android system has gained quite acceptance because of its openness of the source code and novelty for applications. This dissertation applies the Android platform to a handled medical photoacoustic system, and the emphasis is the collection, conditioning and display of photoacoustic signal on the smartphone with the Android system. The hardware platform for signal display reported in this dissertation is the Huawei Y300. The software development environment is Eclipse. Before processing in the smartphone system, the photoacoustic signal is first amplified and conditioned through a hardware circuit. This dissertation also reports the design and simulation of this circuit. The audio input of the mobile phone provides a communication channel for signals. The UI design for this application appliesLinearlayout and widgets like SurfaceView, Button and Zoomcontrols. Overall, this easy and convenient application is suitable for hand-held operation.